MUCOLYTIC TREATMENT OF PROLONGED DISEASES OF RESPIRATORY SYSTEM IN CHILDREN - N.D. Soroka ("Paediatrician" Publishers LLC, 2008)
The structure of morbidity of respiratory system diseases (RSD) in children, living in Saint Petersburg, is described in this article; also the role of prolonged types of RSD is indicated. Main etiologic factors of prolonged RSD are presented, and short clinical characteristics of prolonged RSD are given. Main methods of treatment of negative course of bronchopulmonary diseases are indicated. The data of 35=year clinical experience of use of n-acetylcysteine (fluimucil) in children is presented. It was marked, that n-acetylcysteine has significant complex mucolytic effect in children with RSD. Key words: children, diseases of respiratory system, prolonged types, n-acetylcysteine, treatment.